Development of bioanalytical assays for variegin, a peptide-based bivalent direct thrombin inhibitor. (May 2017) - Shih, Norrapat; de Carvalho, Leonardo Pinto; Lee, Yie Hou; Rocha, Mauricio Macario; Pereira Barbosa, Adriano Henrique; A de Sousa, José Marconi; de C Carvalho, Antonio Carlos; Kini, R Manjunatha; Chan, Mark Y
Aim: Variegin is an anticoagulant peptide that will be tested in porcine models of percutaneous coronary intervention. We developed three bioanalytical assays for variegin quantitation and utilized these methods to evaluate pharmacokinetics of variegin in pigs.Results & methodology: The LC–MS/MS, thrombin amidolytic and modified thrombin time assays had a quantitation range of 21.6–5541.7, 10.8–5541.7 and 5.4–5541.7 nM in human plasma, respectively. The elimination half-lives obtained using the LC–MS/MS, modified thrombin time and thrombin amidolytic assays were 52.3 ± 4.4, 50.4 ± 5.9 and 67.7 ± 6.3 min, respectively.Conclusion: We developed three bioanalytical assays for a novel direct thrombin inhibitor, variegin. The thrombin time assay is optimized for variegin quantitation during future porcine studies and clinical trials.